2019
DOI: 10.1111/fcp.12437
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetylcysteine prevents glutathione decrease and does not interfere with paracetamol antinociceptive effect at therapeutic dosage: a randomized double‐blind controlled trial in healthy subjects

Abstract: Paracetamol (APAP) may lead to hepatic changes even at therapeutic dosages. Glutathione (GSH) plays a pivotal role in APAP metabolism as it allows the detoxification of a toxic metabolite. N‐Acetylcysteine (NAC) is APAP antidote, is also largely used as a mucoactive drug and is often associated with APAP. This study aims at evaluating if 1‐ NAC modifies APAP pain efficacy and 2‐ NAC prevents glutathione depletion with APAP at therapeutic doses. This double‐blind randomized controlled study (NCT02206178) was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all RCTs and meta-analyses reported numbers of adverse events from paracetamol that were inferior to those of NSAIDs and comparable to those of placebo. However, reviews on long-term observational data reported increased cardiovascular, gastrointestinal, and renal adverse events during therapy with paracetamol, especially in the high dose range; cases of acute liver failure have been reported after accidental and unintentional overdose of paracetamol [ 10 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 ]. Acute liver failure is infrequent with an approximate incidence for all causes of 1/million/year and is declining [ 134 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…N-acetyl cysteine has been widely used as a glutathione regenerator to treat paracetamol overdoses, and several other molecules are under investigation to treat paracetamol-induced liver damage [ 139 , 140 , 141 ].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…Consistently, Heard et al [ 88 ] showed that NAC loading at 140 mg/kg, followed by 70 mg/kg every 4 h for 12 doses, could reduce the rate of hepatotoxicity and adverse events in patients with history of acute acetaminophen ingestion within the 24 h preceding emergency department evaluation. Alternatively, Pickering et al [ 89 ] showed that an even higher dose of NAC at 300 mg twice daily, given concurrently with paracetamol at 1 g daily for 4 days, could neutralize paracetamol-induced hepatic toxicity, in part, by maintaining GSH levels.…”
Section: Protective Effects Of N-acetyl Cysteine Against Drug-induced Liver Injurymentioning
confidence: 99%
“…This also includes exposures to nonessential inputs that may impact performance. A brief summary of selected influences is considered below: Nutrient loss from extreme training or operations (e.g., magnesium loss through sweating via exertion in hot environments; Institute of Medicine (US) Committee on Military Nutrition Research Bernadette M. Marriott, 1993 ) Nutrient needs that increase due to the operating environment or operational demands (Longland et al, 2016 ) Medication use that increases nutrient demands by consuming phase II conjugation agents or nutrient loss through excretion (Pickering et al, 2019 ; Beger et al, 2020 ; Kim et al, 2021 ) Medication use that impairs the synthesis of metabolically essential compounds (e.g., statins and ubiquinone), rendering them conditionally essential (Marcoff and Thompson, 2007 ) Exposure to environmental xenobiotics that place additional burden on metabolic networks, detoxification pathways, and nutrient cofactor pools (e.g., sulfur-bearing amino acids; Barros et al, 2021 ) Reabsorption of metabolites derived from the gut microbiome that compete for critical nutrients, such as sulfhydryl compounds (e.g., p -cresol and glutathione; Schmidt et al, 2022 ) Deficits in gut microbiome-derived critical nutrients (e.g., β-hydroxybutyrate needed to maintain colonic barrier integrity and brain epigenetic regulation; Silva et al, 2020 ) Exposure to environmental xenobiotics that poison enzyme systems (e.g., arsenic complexing with the alpha-lipoic acid residues on the pyruvate dehydrogenase complex, thus disrupting the TCA cycle and energy metabolism) (Schiller et al, 1977 ; Nurchi et al, 2020 ) Illicit drug use that modifies molecular networks (Patkar et al, 2009 ) Specialized diets that lead to deficits unique to the diet (e.g., ketogenic, vegan, vegetarian, intermittent fasting, caloric restriction, caloric excess; Calton, 2010 ; Thomas et al, 2016 ; Churuangsuk et al, 2019 ) Genetic variants (SNPs) that modify specific nutrient requirements (e.g., MTHFR and B12/folate/riboflavin; FAD1 and EPA/DHA; PEMT and choline; HFE and iron; Mathias et al, 2014 ; Amenyah et al, 2020 ) …”
Section: What Is the Origin Of Input Deficits In Generally Healthy Op...mentioning
confidence: 99%